A Compendium of in vitro Germination Media for Pollen Research - Tushabe, Donam; Rosbakh, Sergey (Frontiers in Plant Science, 2021)
The correct choice of in vitro pollen germination media (PGM) is crucial in basic and applied pollen research. However, the methodological gaps (e.g. strong focus of current research on model species and cultivated plants along with the lack of general rules for developing a PGM) makes experimenting with pollen difficult. We closed these gaps by compiling a compendium of optimised in vitro PGM recipes from more than 1800 articles published in English, German and Russian from 1926 to 2019. The compendium includes 1572 PGM recipes successfully used to germinate pollen grains or produce pollen tubes in 816 species representing 412 genera and 114 families (both monocots and dicots). Among the 110 components recorded from the different PGM recipes, sucrose (89% of species), H3BO3 (77%), Ca2+ (59%), Mg2+ (44%), and K+ (39%) were the most commonly used PGM components. Also, we identified some general rules for creating PGM for various groups of species differing in area of research (wild and cultivated species), phylogenetic relatedness (angiosperms vs. gymnosperms, dicots vs. monocots), pollen physiology (bi- and tricellular), biochemistry (starchy vs. starchless pollen grains) and stigma properties (dry vs. wet), and compared the component requirements. Sucrose, calcium and magnesium concentrations were significantly different across most categories indicating that pollen sensitivity to sugar and mineral requirements in PGM is highly group-specific and should be accounted for when composing new PGM. This compendium is an important data resource on PGM and can facilitate future pollen research.